2019
DOI: 10.1002/open.201900094
|View full text |Cite
|
Sign up to set email alerts
|

Ylide‐Functionalization via Metalated Ylides: Synthesis and Structural Properties

Abstract: The α‐metallated ylides [Ph3P−C−Z]−M+ (with Z=SO2Tol or CN and M=Na or K) were used as versatile nucleophiles for the facile access to ylide‐substituted compounds. Halogenations, alkylations, carbonylations and functionalization reactions with main group element halides were easily accomplished by simple trapping reactions with the appropriate electrophiles. X‐ray crystallographic studies of all compounds – including the first structures of α‐fluorinated P‐ylides – showed remarkable differences in the ylide ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…7 ). 63 Although these phosphines have been known for quite some time, 64,65 their strong donor properties owing to the electron donation from the ylide to the phosphorus centre were only recently recognized. Our group used YPhos ligands as electron-rich phosphines in homogeneous catalysis, which led to highly active gold and palladium catalysts e.g.…”
Section: Ylide-stabilized Group 15 Compoundsmentioning
confidence: 99%
“…7 ). 63 Although these phosphines have been known for quite some time, 64,65 their strong donor properties owing to the electron donation from the ylide to the phosphorus centre were only recently recognized. Our group used YPhos ligands as electron-rich phosphines in homogeneous catalysis, which led to highly active gold and palladium catalysts e.g.…”
Section: Ylide-stabilized Group 15 Compoundsmentioning
confidence: 99%
“…Until today, only five metalated ylides have been isolated and also structurally characterized (Figure ), whereat only 1‐M and 2‐M (with M = Li, Na, K) have been prepared in gram‐scale and applied in synthesis. For example, our group demonstrated that 1‐M and 2‐M are excellent reagents for ylide‐functionalizations, which represents a powerful tool for the electronic manipulation of main group compounds.,, As such, electron‐deficient species like borenium ions and tetrylenes were successfully isolated starting from 1‐Na . Likewise, a series of ylide‐substituted phosphines were prepared which turned out to be excellent ligands for homogeneous catalysis …”
Section: Introductionmentioning
confidence: 99%
“…[5] Since then, a number of metallated ylides (compounds B‐E ) have been isolated [6] – partly also on a gram scale – and applied in ylide transfer reactions. [7] Our group, for example, isolated the sulfonyl‐substituted compounds D and used them for the stabilization of low‐valent main group species [8] as well as in the synthesis of ylide‐substituted phosphines, which revealed themselves to be powerful ligands for homogeneous catalysis. [ 9 , 10 ]…”
mentioning
confidence: 99%
“…[5] Since then, a number of metallated ylides (compounds B-E) have been isolated [6] -partly also on a gram scale -and applied in ylide transfer reactions. [7] Our group, for example, isolated the sulfonyl-substituted compounds D and used them for the stabilization of low-valent main group species [8] as well as in the synthesis of ylide-substituted phosphines, which revealed themselves to be powerful ligands for homogeneous catalysis. [9,10] In order to expand the portfolio of readily accessible metallated ylides for their use in main group chemistry, we became interested in the preparation of further readily isolable and storable yldiides.…”
mentioning
confidence: 99%